Impact of cleft lip closure on the perception of the child by the mother and the social environment – A retrospective, self-reported, standardized pretest. Issue 10 (October 2020) - Scheller, Konstanze; Urich, Jasmin; Watzke, Stephan; Scheller, Christian; Haase, Roland
Abstract: The aim of the study was to describe the attractiveness of a newborn with CL/P and the maternal reaction in relation to the child. Another purpose was to explore and describe the experience and subjectively perceived reaction of the mother and the social environment to the child before and after cleft lip surgery. Material and methods: A study to describe and evaluate mothers' experiences, feelings and emotions (n = 84) regarding having a child with CL/P was performed. Therefore mothers were asked to complete a self-reported, standardized Likert-scale questionnaire. The questions were focused on the mother's own experiences, and the reaction of close family members and the social environment (friends, unknown people) to the child. Therefore two essential situations during the first year of life were analyzed: the first contact with the child, and a second one after lip surgery. The influence of lip reconstruction on the attractiveness of the child and the following reactions were analyzed. The timeline includes surveys from 01/2014 to 12/2016. Results: 84 mothers of affected children (CL/P) replied to the questionnaire (84/103). Most mothers (n = 64) described the attractiveness of their child at birth as "very good" (n = 37) and "good" (n = 27). After lip reconstruction the subjective attractiveness in the mothers' opinions increased to 90.5% (n = 76): 24 "good" (p = 0.23) and 52 "very good" (p = 0.73). 50 mothers defined the postoperative surgical result as "very good", 21 did not see any improvement (p = 0.001). Poor postoperative evaluations like "very poor" (n = 0), "insufficient" (n = 1) or "sufficient" (n = 1) were found two times. The majority of mothers (n = 78) reported negative reactions of the social environment to the child before lip surgery. Friends reacted in general more positively to the child with the visible deformity than did the social environment. 41 mothers described that their life partner or husband reacted "always" more positively to the child (p = 0.018). After surgical lip closure, strangers (n = 22) and even friends (n = 27) did not change their reactions obviously. Conclusion: For the mother, the attractiveness of a child with CL/P is not significantly affected by the visible facial malformation. Even if the lip reconstruction increases the child's attractiveness from the mother's perspective, the often negative reactions of the family and social environment did not change.